ARTFUL NAIVETÉ. NOTES ON THE POETRY COLLECTIONS MEZI NÁMA AND BETONOVÁ PLÁŽ BY ŠIMON LEITGEB - Lukáš, Martin (Bohemica Olomucensia, 2023)
Promising Czech poet Šimon Leitgeb (born 1996) has received rather favourable reviews of his two poetry collections published so far, i.e., Mezi náma (Among Us, 2017) and Betonová pláž (The Cement Beach, 2020), the second of which Leitgeb was given the Jiří Orten Award for, a Czech literary prize for young authors under the age of 30. Almost all of the reviewers recognized "naiveté" as a constitutional quality of Leitgeb's poetry. However, too few of them saw this "naiveté" as part of the author's cunning stylization, or an artful means of arousing readers' sympathy for or bringing their attention to the characters and situations as depicted in the poems by the fictional speaker, himself being "naïve" in particular.
Keywords: Šimon Leitgeb; Mezi náma; Betonová pláž; Czech poetry; naiveté; fictional speaker